Prepaint specialties and surface tolerant coatings - Flick, Ernest W. (Noyes Publications, 1991)
This book describes over 1500 prepaint specialties and surface tolerant coatings supplied by 67 manufacturers or distributors of these products. The products described may, for example, prepare the surface for paint, thin the paint, allow painting over rusted areas, or provide quick and easy cleanup. They may be fillers, sealers, rust preventives, galvanizers, caulks, grouts, glazes, phosphatizers, corrosion inhibitors, neutralizers, graffiti removers, floor surfacers, etc. The book lists the following Product Information, as available, in the manufacturer's own words: Company Name, Product Category, Trade Name and Product Number, Product Description. It also contains a Trade Name Index, and a list of Suppliers' Addresses.
Includes indexes.
Keywords: Primers (Coating); Sealing compounds.; elektronické knihy; electronic books